Efficient promotion of renewable energy with reverse auctions - Sebastian Schäfer; Lisa Schulten (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
Despite negative experiences with auctioning off subsidies for renewable energy in some countries, tenders are increasingly used today. We develop a reverse auction which accounts for particularities of intermittent renewable energy sources. Determining the quantity, demanded by the regulator, is internalized and directly linked to his two main objectives. On the one hand, the regulator seeks for a high share of renewable energy. On the other hand, he wants to enhance burden sharing between electricity consumers and renewable electricity producers. We further account for asymmetric information in reverse auctions. We analyze incentives for bidders to manipulate the auction outcome and adapt the design to prevent this behavior. Regional features as grid and generating capacity can be considered to optimize the deployment of renewable energy. We thereby introduce a link to fossil capacity auctions.
Keywords: C72; D44; D47; D82; L10; Q48; 330; Auction Design; Tendering; Renewable Energy; Adverse Selection; Moral Hazard; Burden Sharing